Reconstitution of Proapoptotic BAK Function in Liposomes Reveals a Dual Role for Mitochondrial Lipids in the BAK-driven Membrane Permeabilization Process - Landeta, Olatz (American Society for Biochemistry and Molecular Biology, 2011)
BAK is a key effector of mitochondrial outer membrane permeabilization (MOMP) whose molecular mechanism of action remains to be fully dissected in intact cells, mainly due to the inherent complexity of the intracellular apoptotic machinery. Here we show that the core features of the BAK-driven MOMP pathway can be reproduced in a highly simplified in vitro system consisting of recombinant human BAK lacking the carboxyl-terminal 21 residues (BAKΔC) and tBID in combination with liposomes bearing an appropriate lipid environment. Using this minimalist reconstituted system we established that tBID suffices to trigger BAKΔC membrane insertion, oligomerization, and pore formation. Furthermore, we demonstrate that tBID-activated BAKΔC permeabilizes the membrane by forming structurally dynamic pores rather than a large proteinaceous channel of fixed size. We also identified two distinct roles played by mitochondrial lipids along the molecular pathway of BAKΔC-induced membrane permeabilization. First, using several independent approaches, we showed that cardiolipin directly interacts with BAKΔC, leading to a localized structural rearrangement in the protein that “primes” BAKΔC for interaction with tBID. Second, we provide evidence that selected curvature-inducing lipids present in mitochondrial membranes specifically modulate the energetic expenditure required to create the BAKΔC pore. Collectively, our results support the notion that BAK functions as a direct effector of MOMP akin to BAX and also adds significantly to the growing evidence indicating that mitochondrial membrane lipids are actively implicated in BCL-2 protein family function.